THE DOCUMENTS REQUIREMENTS FOR EMPLOYING FOREIGN WORKERS: IMPACT ON LOCAL WORKERS IN INDONESIA - Siti Hajati Hoesin; Fitriana Fitriana (UNISSULA, 2022)
This research aims to describe the changes in the provisions on the employment of foreign workers in Indonesia. In order to create job opportunities, through Act No. 11 of 2020 on Job Creation, there is a simplification of the requirements for foreign workers. It is different from the previous one based on Act No. 13 of 2003 on Manpower, which the employment of foreign workers is an exception with certain conditions. This research used a normative juridical method with a statutory approach, it can be concluded that the provisions under Act No. 11 of 2020 on Job Creation which only requires the endorsement of Foreign Workers Utilization Plan to employ foreign workers, make it easier for foreign people to work in Indonesia. As a result, there is intense competition between foreign and local workers. The government is responsible for fulfilling the rights of citizens to obtain work, lest the simplification of foreign workers requirements to work in Indonesia causing violations of the human rights of citizens. Therefore, it is necessary to strive so that local workers are not excluded from foreign workers.